METHODS OF SOLVING THE PATTERN RECOGNITION PROBLEM USING RESIDUE NUMBER SYSTEM - Nikolay Ivanovich Chervyakov; Pavel Alekseyevich Lyakhov; Kirill Sergeyevich Shulzhenko (Наука. Инновации. Технологии, 2022)
The paper proposes a possibility of implementing algorithms of solving the pattern recognition problem in the Residue Number System. Considered the most advanced information processing algorithms in the Residue Number System and performed their comparative analysis. The comparison methods of performing non-modular operations based on Core Function and Mixed Radix Conversion. There is show that using Mixed Radix Conversion does not lead to a signifcant increase in the time complexity of the algorithm when per-forming such non-modular operations as comparison and scaling. Application of non-modular operations, based on the Core Function imposes a limitation on the choice of Residue Number System moduli set, but allows to increase the parallelism of operations for each moduli. There are provide recommendations for using the modular arithmetic algorithms, depending of formulated pattern recognition problem.